CEO personality traits, strategic flexibility, and firm dynamics - Aabo, Tom; Pantzalis, Christos; Park, Jung Chul; Trigeorgis, Lenos; Wulff, Jesper N. (Journal of Corporate Finance, 2024)
Reexamining CEO personality traits from a real options theory perspective, we suggest that the firm's strategic flexibility can be worsened by CEO conscientiousness and neuroticism. We use a measure of strategic flexibility as the firm's ability to take advantage of heightened volatility, which then results in superior stock returns. Our results suggest that strategic adaptability is impeded by rigid planning, resistance to change (conscientiousness) and lack of emotional stability (neuroticism). For firms that experience a decrease in volatility, the opposite holds. In line with trait activation theory, our results imply that the effect of specific CEO personality traits on firm dynamics and performance is contingent and context-specific. Our findings are economically significant and have important implications concerning CEO selection and management.